The Influence of Competence, Motivation, Facilities and Infrastructure, and Leadership Style on Performance and Their Implications for Work Achievement - Yusuf Yusuf (Equity: Jurnal Ekonomi, 2024)
Improving employee performance requires a good strategy, starting with enhancing elements of competence, motivation, adequate facilities and infrastructure support, and a good leadership style, which can improve employee performance and ultimately lead to increased employee achievement, thereby achieving organizational goals. The purpose of this research is to understand the overview of competence, motivation, facilities and infrastructure, leadership style, performance, and work achievement, as well as to determine the influence of competence, motivation, facilities and infrastructure, and leadership style on performance and their implications for work achievement. The subjects of this research are the Civil Servants of the Ministry of Religious Affairs Office of the Bangka Belitung Islands Province. The research method uses a descriptive and verification approach with descriptive survey and explanatory survey methods. The sample consists of 91 people, using primary data. Path analysis techniques are employed. The results of the research show that: (1) All variables have high average values, ranging from 4.11 to 4.37. The performance variable has the highest average at 4.37, and the X2 motivation variable has the highest average at 4.28. In general, competence, motivation, facilities and infrastructure, leadership style, performance, and work achievement are rated highly. Correlation test results show (R) 0.787 and the coefficient of determination of variable X on variable Y (R2) is 62%, with the remaining (E) 38%, and for variable Y on variable Z (R2) 85.2%, with the remaining 14.8% influenced by other factors not examined. (2) Simultaneously, competence, motivation, facilities and infrastructure, and leadership style significantly influence performance (35.049 > 2.477). (3) Partially, there is a significant influence of competence (-2.370 > -1.986), motivation (6.053 > 1.986), and leadership style (3.644 > 1.986) on performance, while there is no influence of facilities and infrastructure on performance (1.002 < 1.986). (4) There is a significant influence of performance on work achievement (22.591 > 1.986).